1994
DOI: 10.1089/neu.1994.11.599
|View full text |Cite
|
Sign up to set email alerts
|

Modification of the Cortical Impact Model To Produce Axonal Injury in the Rat Cerebral Cortex

Abstract: Diffuse axonal injury (DAI) is a form of brain injury that is characterized by morphologic changes to axons throughout the brain and brainstem. Previous biomechanical studies have shown that primary axonal dysfunction, ranging from minor electrophysiologic disturbances to immediate axotomy, can be related to the rate and level of axonal deformation. Some existing rodent head injury models display varying degrees of axonal injury in the forebrain and brainstem, but the extent of axonal damage in the forebrain h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(41 citation statements)
references
References 13 publications
1
40
0
Order By: Relevance
“…Direct visualization of grid patterns or embedded markers within a transparent silicone gel also provided direct evidence for the unique patterns of deformations that occur with accelerations imposed in different directions and the influence that different skull/gel boundary conditions and ventricular structures have on intracranial strains, showing that the ventricles can redistribute and, in some regions, reduce the strains appearing within the brain after impact [99][100][101][102]. In some instances, these models have been used to assess the effectiveness of different animal models to recreate the deformation patterns that appear during impact and have led to a redesign of animal models to produce deformation patterns that more closely resemble the strains within the hemispheres during injury [103][104][105]. These same techniques are now extended to blast loading conditions [102][103][104][105][106][107][108][109], where the efforts will yield significant information on the manner that external blast waves transfer to the brain simulant, how these pressures are distributed throughout the surrogate, and how these pressures dissipate over time.…”
Section: An Integrated Multiscale Approach For Understanding Traumatmentioning
confidence: 99%
See 1 more Smart Citation
“…Direct visualization of grid patterns or embedded markers within a transparent silicone gel also provided direct evidence for the unique patterns of deformations that occur with accelerations imposed in different directions and the influence that different skull/gel boundary conditions and ventricular structures have on intracranial strains, showing that the ventricles can redistribute and, in some regions, reduce the strains appearing within the brain after impact [99][100][101][102]. In some instances, these models have been used to assess the effectiveness of different animal models to recreate the deformation patterns that appear during impact and have led to a redesign of animal models to produce deformation patterns that more closely resemble the strains within the hemispheres during injury [103][104][105]. These same techniques are now extended to blast loading conditions [102][103][104][105][106][107][108][109], where the efforts will yield significant information on the manner that external blast waves transfer to the brain simulant, how these pressures are distributed throughout the surrogate, and how these pressures dissipate over time.…”
Section: An Integrated Multiscale Approach For Understanding Traumatmentioning
confidence: 99%
“…In some instances, these models have been used to assess the effectiveness of different animal models to recreate the deformation patterns that appear during impact and have led to a redesign of animal models to produce deformation patterns that more closely resemble the strains within the hemispheres during injury [103][104][105]. These same techniques are now extended to blast loading conditions [102][103][104][105][106][107][108][109], where the efforts will yield significant information on the manner that external blast waves transfer to the brain simulant, how these pressures are distributed throughout the surrogate, and how these pressures dissipate over time. Although providing a direct window into the possible response of the brain to any external mechanical loading condition, it is worth noting that the highly elastic material properties of brain tissue surrogates will need to be considered in extending or interpreting these results for the viscoelastic, nonlinear brain tissue.…”
Section: An Integrated Multiscale Approach For Understanding Traumatmentioning
confidence: 99%
“…It has been shown that the presence of bilateral craniectomies shifts intracranial strain distribution to the contralateral hemisphere and causes increased contralateral axonal damage. 41,42 As such, bilateral Craniectomies were chosen in order to increase the likelihood of contralateral hippocampal damage. Rats received a single impact (2.5-mm deformation) on the right parietal lobe with an impact velocity of 5 m/sec.…”
Section: Production Of Cortical Impact Injury and Drug Administrationmentioning
confidence: 99%
“…Among these papers, 122 papers reported the use of a unilateral (single) craniotomy, 17 papers reported bilateral craniotomy use, while 95 papers did not report this information. In one unique study, both unilateral and contralateral craniotomies were studied (Meaney et al 1994). Among the 222 papers in which the impact depth was reported, 12 papers utilized two depth levels and six reported three depth levels.…”
Section: Review Of External CCI Impact Parameters In the Literaturementioning
confidence: 99%